Bacterial meningitis knowledge, attitude and practice study among parents: a cross-sectional study - Jbari, Siham; El-Mouhdi, Karima; El Omari, Hajar; Bourrous, Mounir; Boussaa, Samia (International Journal of Public Health Science (IJPHS), 2025)
In Morocco, bacterial meningitis has consistently posed a significant public health challenge. Addressing this issue requires a deeper understanding of public perceptions to enhance awareness and prevention efforts. This quantitative cross-sectional study, conducted in health facilities in the Marrakech-Safi region from May 2022 to January 2023, employed Cronbach's Alpha with a reliability score of 72% to analyze the association between knowledge levels and various factors. The research revealed that the majority of participants were aged between 20 and 30 years (51.8%) and female (64.4%). The term most commonly used by Moroccans to describe purulent meningitis was “bad fever” (Skhana lkhayba), with 68.8% using this term. Additionally, 82% of participants had an average level of knowledge about the disease. Analysis indicated that families with four children demonstrated a higher level of knowledge compared to those with fewer or more children (p = 0.048). Participants residing in structured housing had a lower level of knowledge than those in unstructured housing (p = 0.017). Furthermore, educational attainment at the primary and secondary school levels was significantly associated with knowledge levels (p = 0.020 and p = 0.015, respectively). Understanding public perceptions and vulnerabilities related to bacterial meningitis can significantly improve disease control and prevention strategies.